GAMELAN GONG BERI IN BALINESE CULTURE - Gede Yoga Kharisma Pradana; I Putu Agus Eko Sattvika; Kadek Angga Wahyu Pradana (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The purpose of research on Gamelan Gong Beri is to reveal the role of the existence of Gamelan Gong Beri in the context of Balinese culture. Gamelan Gong Beri has been recognized for a long time as a traditional Balinese musical instrument. However, not all Balinese recognize the role of Gamelan Gong Beri in carrying out Balinese cultural activities. The questions are : 1) Where is the Origins of Gamelan Gong Beri in Balinese Culture? 2) How is the existence of Gamelan Gong Beri in Balinese Culture?. This research was conducted using qualitative methods. The results showed that : 1) the beginning of the existence of Gamelan Gong Beri as a traditional Balinese musical instrument from Renon, Denpasar, Bali based on Blanjong inscriptions and legends in the history of Gamelan Gong Beri. 2) The existence of Gamelan Gong Beri in the activities of sustainable Balinese Culture in accompanying the Baris Cina dance performance in the traditional ceremonies in Renon, Denpasar, Bali. The implications of the research results confirm that the Gamelan Gong Beri is an artifact of historical value that has the potential to become a vital means for the preservation of Balinese culture and cultural creation if it receives attention from the community and cultural agents.